Autonomic functioning in reactive versus proactive aggression: The influential role of inconsistent parenting. Issue 5 (24th July 2018) - Kassing, Francesca; Lochman, John E.; Glenn, Andrea L.
Abstract : Research has consistently supported autonomic nervous system (ANS) functioning as a predictor of aggressive behavior in youth. Several studies have further examined how the functioning of the sympathetic (SNS) and parasympathetic (PNS) branches of the ANS interact with environmental factors to predict behavioral outcomes. One factor that has yet to be studied in this context however, is parenting practices. Given that many interventions for externalizing behavior target parenting practices, such as increasing consistent discipline, it may be particularly important to assess whether parenting practices interact with SNS and PNS functioning in the child to influence risk for aggressive behavior. Therefore, the current study addressed this question by examining inconsistent discipline as a moderator of the relationship between baseline SNS versus PNS activity and reactive versus proactive aggression. Data were collected from a sample of fourth graders identified as at‐risk for aggression ( N = 188). Results indicated that baseline SNS activity was positively related to proactive aggression under high levels of inconsistent discipline, but negatively related to proactive aggression under very low levels of inconsistent discipline. Baseline PNS activity was negatively associated with reactive aggression under low levels of inconsistent discipline. No main effects were found for SNS or PNS functioning and either form of aggression, emphasizing the importance of taking a biosocial approach to examining the predictors of aggressive behavior in at‐risk youth. Results from this study help to better understand the circumstances under which children are most likely to exhibit reactive versus proactive aggression, better informing targeted prevention and treatment.